1989
DOI: 10.1073/pnas.86.6.1987
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus-infected T cells and monocytes are killed by monoclonal human anti-gp41 antibodies coupled to ricin A chain.

Abstract: Two human monoclonal antibodies specific for the envelope glycoprotein (gp), gp4l, of the human immunodeficiency virus were conjugated to deglycosylated ricin A chain. These immunotoxins killed human immunodeficiency virus-infected H9 (T cell) and U937 (monocyte) cell lines but were nontoxic to the uninfected cell lines or to class II-positive Daudi cells. Specific killing of infected H9 cells could be completely blocked by recombinant gpl6O and partially blocked by unconjugated anti-gp4l antibody but was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Preliminary studies suggest that they neither neutralize nor enhance virus infectivity (E. Robinson, W. Mitchell, M.K.G., and S.Z.-P., unpublished data). However, when coupled to deglycosylated ricin A chain, at least two of the Abs, 50-69 and 98-6, specifically kill HIV-infected cells (41). Thus, the Abs have sufficiently high affinity to bind to antigen immobilized on various matrices and to bind to antigen on the Immunology: Gorny et al…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary studies suggest that they neither neutralize nor enhance virus infectivity (E. Robinson, W. Mitchell, M.K.G., and S.Z.-P., unpublished data). However, when coupled to deglycosylated ricin A chain, at least two of the Abs, 50-69 and 98-6, specifically kill HIV-infected cells (41). Thus, the Abs have sufficiently high affinity to bind to antigen immobilized on various matrices and to bind to antigen on the Immunology: Gorny et al…”
Section: Resultsmentioning
confidence: 99%
“…The addition of sCD4 destabilizes the gp120-gp41 interaction, resulting in greater exposure of this otherwise partially obscured epitope. Others have also targeted this region (11,19). A different group of investigators has focused on the CD4-binding site (CD4bs) as the target of choice (10,14,15,17,18,20).…”
Section: Importancementioning
confidence: 99%
“…Most studies with anti-HIV monoclonal antibodies (MAbs) have examined the neutralization of cell-free virus (1)(2)(3)(4) or the prevention of intercel-lular transmission (5). In reality, MAbs likely exert anti-HIV effects in multiple ways, including by prevention of cellular infection; targeting of infected cells, including FcR-positive cells or complement, for destruction by Fc-mediated effects (6)(7)(8)(9); or delivery of a toxic payload to cells in the form of immunoconjugates (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). It is often assumed that the same MAbs that prevent the transmission of infection are also the most effective in eliminating persistently infected cells (21,22), despite evidence to the contrary (6,13,16,19).…”
Section: Importancementioning
confidence: 99%
“…They may be targeted either to cell types known to be sites of HIV replication (1)(2)(3) or to actively infected cells expressing the HIV envelope protein(s) gp160, gp120, and gp41 on the cell surface. These anti-HIV ITs may be targeted with either CD4 (4 -6) or with mAbs (7)(8)(9)(10). In vitro studies have shown that anti-HIV ITs are among the most effective antiviral agents tested (11,12), with efficacy against multiple cell types, including macrophages (13), and against a variety of HIV isolates (10,14).…”
mentioning
confidence: 99%